Determinants of Structure of Corporate Governance Disclosure in Portugal - Cunha, Vera; Rodrigues, Lúcia Lima (Review of Business Management, 2018)
Purpose – This study analyses the determinants of the level of corporate governance disclosure (CGD) by Portuguese companies listed on Euronext Lisbon between 2005 and 2011. Design/methodology/approach – Using content analysis, we construct a corporate governance index for each firm based on the data extracted from the firm’s corporate governance and annual reports. An ordinal logistic regression model is used to examine the relationship between the level of CGD and its determinants. Findings – The empirical evidence suggests that foreign investor ownership, board size, board independence, external audit quality and degree of internationalization had a significant and positive influence on the corporate governance disclosure level, whereas ownership concentration, unitary leadership structure and debt had a significant and negative influence on corporate governance disclosure. No results were observed for board of director ownership and manager stock option compensation variables. Originality/value – This study extends the previous literature by examining corporate governance disclosure. Moreover, it extends prior work by analysing foreign investor ownership, manager stock option compensation and degree of internationalization as determinants of information disclosure. Finally, we believe that this study, conducted over a longer period of time, might give us stronger statistical evidence.